In Vivo 31P-Nuclear Magnetic Resonance Studies of Glyphosate Uptake, Vacuolar Sequestration, and Tonoplast Pump Activity in Glyphosate-Resistant Horseweed. Issue 3 (2nd September 2014) - Ge, Xia; d'Avignon, D. André; Ackerman, Joseph J.H.; Sammons, R. Douglas
Abstract : Rapid vacuole sequestration, the glyphosate resistance mechanism observed in glyphosate-resistant horseweed, is associated with plasma membrane and tonoplast ATP-binding cassette transporters . Abstract: Horseweed ( Conyza canadensis ) is considered a significant glyphosate-resistant (GR ) weed in agriculture, spreading to 21 states in the United States and now found globally on five continents. This laboratory previously reported rapid vacuolar sequestration of glyphosate as the mechanism of resistance in GR horseweed. The observation of vacuole sequestration is consistent with the existence of a tonoplast-bound transporter. 31 P-Nuclear magnetic resonance experiments performed in vivo with GR horseweed leaf tissue show that glyphosate entry into the plant cell (cytosolic compartment) is (1) first order in extracellular glyphosate concentration, independent of pH and dependent upon ATP; (2) competitively inhibited by alternative substrates (aminomethyl phosphonate [AMPA ] and N -methyl glyphosate [NMG ]), which themselves enter the plant cell; and (3) blocked by vanadate, a known inhibitor/blocker of ATP-dependent transporters. Vacuole sequestration of glyphosate is (1) first order in cytosolic glyphosate concentration and dependent upon ATP; (2) competitively inhibited by alternative substrates (AMPA and NMG ), which themselves enter the plant vacuole; and (3) saturable. 31 P-Nuclear magnetic resonance findings with GR horseweed are consistent with the active transport of glyphosate and alternative substrates (AMPA and NMG ) across the plasma membrane and tonoplast in a manner characteristic of ATP-binding cassette transporters, similar to those that have been identified in mammalian cells.